The Role Of Entamoeba Gingivalis In Periodontal Disease: A Literature Study - Emma Rachmawati; Rizky Farida Berlian; Ina Hendiani; Nuroh Najmi; Achmad Syawqie (Sean Institute, 2023)
Background: Periodontal disease can affect the supporting structures of the teeth and can cause tooth loss. Periodontal disease is caused mainly by bacteria in dental plaque, but protozoa can also be found in deep pockets. The most common protozoa existing in periodontal disease is Entamoeba gingivalis. This study aims to determine the role of E. gingivalis in periodontal disease. Method: This research was a rapid review which is a method of synthesizing and assessing existing research. Articles were searched using the PubMed database from February 2021 to April 2021 with inclusion criteria in English from 2010 to 2020 and discussing the presence of E. gingivalis in periodontal disease. Result: Articles that comply with the inclusion criteria of this study are 11 articles. The study designs included case-control, cross-sectional, cohort, and case series. All articles concluded that E. gingivalis was found in patients with periodontal disease. Conclusion: The presence of E. gingivalis in large numbers in inflamed periodontal tissues indicates that E. gingivalis has a role in the course of periodontal disease.